A participatory architecture for taxation and budgeting. (9th December 2008) - Kalikakis, Manolis; Gouscos, Dimitris; Georgiadis, Panagiotis
This paper is positioned at the intersection of two important fields: e-taxation services and Participatory Budgeting (PB). E-taxation has traditionally been considered to be a solution to the bureaucracy and non-transparency of tax filing and payment; however, it does not account for the way in which taxes are used. In addition to evaluating the availability of public funds, PB includes decisions on fund allocation. Our approach combines these two important aspects of taxation and fund allocation in a unified e-participation scheme, where the entire life cycle of public funds collection and spending is transparent. This approach incorporates software tools and operational workflows that give citizens a holistic view of how public funds are collected and used.